Coping Skill Mahasiswa Bimbingan Skripsi (Studi Pada Mahasiswa Prodi Informatika Universitas Dehasen Bengkulu) - Nurliyanti, Rani; Narti, Sri; Maryaningsih, Maryaningsih (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This research aims to determine the coping skills used by informatics students in thesis guidance. The research method used was a qualitative descriptive approach with in-depth interview techniques with four students who were active in thesis guidance and two thesis supervisors as sources of information in the research. The theory used is the stress coping theory from Lazarus & Folkman 1984. The results of the research show that informatics students of the Informatics Study Program are more likely to focus on problems (problem-focused coping) such as preparing a regular work schedule, discussing with seniors or friends, fighting feeling lazy, and looking for additional references from previous research journals or websites that support learning, because not all Informatics students have the ability to manage emotions (emotion-focused coping) such as seeking support from friends and family, not easily getting emotional when the lecturer is angry when don't reply to chats, be patient, don't panic, don't give up easily trying to carry out guidance and remain enthusiastic especially when experiencing pressure during thesis guidance.